A COMPREHENSIVE ASSESSMENT OF SEPTAGE MANAGEMENT IN BANTUL, YOGYAKARTA - Adelia Anju Asmara; Suphia Rahmawati; Andik Yulianto; Margita Rahayu Abay; Dilla Arlina; Dhandhun Wacano (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2021)
Aim: This study aims to assess the entire process of septage management comprising regulation, operational procedures, finance, community involvement, and water quality analysis to maximize the initial and hugest human fecal sludge treatment called Faecal Sludge Treatment Plant (IPLT) in Yogyakarta. Methodology and Results: The Modified EHRA (Environmental Health Risk Assessment) method was applied which focused only on wastewater treatment aspect. Several regulations including standard quality methods (SNI) were utilized and made a comparison between baseline rules and obtained results. Furthermore, quality assessment was accomplished by observation and interview. The results showed that the human sector needs to improve not only the amount of operators but also urgently put up protective personal equipment during the suction process. The dissemination of attractive information about sludge suction service done by PUPKP as a representation of the local government among the dwellers ought to upgrade a lot. Technologies employed which are carriage transportation and vacuum machine, are good enough. Contrarily, septage treatment plants require extra-effort to enhance it as most water quality parameters barely meet the standard quality. BOD, COD, ammonia, total coliform, oil and grease do not meet the third class of water quality (Government Regulation of Republic of Indonesia No. 82/2001). Subsequently, the effectiveness of each unit i.e. anaerobic tank and stabilization ponds are under 50% and the loading rate has a maximum capacity of 87.5m3/day, and 60m3/day minimum capacity. Conclusion, significance and impact of study: Therefore, almost all aspects of septage management in Bantul Yogyakarta are required to improve